A Printed LPDA Antenna Fed by a Microstrip Line to Double Sided Parallel Strip Line from Backside - Zhou Yang; Huang Jingjian; Wu Weiwei; Yuan Naichang (International Journal of Antennas and Propagation)
A novel planar printed log-periodic dipole array (LPDA) antenna fed by tapered microstrip line (MSL) to double sided parallel strip line (DSPSL) is proposed in this paper. The proposed antenna adopts MSL feeding approach from backside. Using this feeding technique makes the printed LPDA antenna easier to be integrated into radio frequency (RF) circuits. In this paper, four layers are used to construct the antenna. The four layers of the printed LPDA antenna are printed on three thin dielectric substrates which are integrated together. To validate this approach, a printed LPDA antenna is simulated and fabricated for operating in the S and C bands (2.5–6 GHz). The antenna showed a good result over the whole frequency range with 2 : 1 VSWR, an average gain of 6.5 dB, and stable radiation patterns. The measured results are in very good agreement with simulations.